2021
DOI: 10.1101/2021.05.31.21258081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Favorable outcome on viral load and culture viability using Ivermectin in early treatment of non-hospitalized patients with mild COVID-19 – A double-blind, randomized placebo-controlled trial

Abstract: Background: Ivermectin, an antiparasitic agent, also has antiviral properties. Our aim was to assess whether ivermectin can shorten the viral shedding in patients at an early stage of COVID19 infection. Methods: The double blinded trial compared patients receiving ivermectin 0.2 mg/kg for 3 days vs. placebo in non-hospitalized COVID19 patients. RT-PCR from a nasopharyngeal swab was obtained at recruitment and then every two days. Primary endpoint was reduction of viral-load on the 6th day (third day after te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Its proposed antiviral mechanism is thought to be mediated by its ability to inhibit the nuclear import of viral proteins mediated by IMPa/b1 heterodimer, and the promotion of defense mechanisms such as pyroptosis in infected epithelial cells, suggesting its possible role as a broad spectrum antiviral agent (30,31). Although an immunomodulatory effect of IVM has been proposed by other authors (32), these effects might explain the antiviral activity against SARS-CoV-2 reported by our group and Biber et al, in two small randomized controlled trials (17,19). However, randomized clinical trials published on this topic have shown a lack of efficacy regarding clinical outcomes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Its proposed antiviral mechanism is thought to be mediated by its ability to inhibit the nuclear import of viral proteins mediated by IMPa/b1 heterodimer, and the promotion of defense mechanisms such as pyroptosis in infected epithelial cells, suggesting its possible role as a broad spectrum antiviral agent (30,31). Although an immunomodulatory effect of IVM has been proposed by other authors (32), these effects might explain the antiviral activity against SARS-CoV-2 reported by our group and Biber et al, in two small randomized controlled trials (17,19). However, randomized clinical trials published on this topic have shown a lack of efficacy regarding clinical outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…However, after over a year of several publications addressing this question, there is a lack of clear evidence for or against the use of IVM in COVID-19 patients (6,14). With at least two completed double-blind randomized clinical trials (RCTs) showing no effect in clinical endpoints, other smaller randomized trials using higher doses identified significant antiviral effects (15)(16)(17)(18)(19) or a reduction in the clinical signs, including anosmia (20). That undefined landscape is summarized by the current NIH COVID-19 treatment Guidelines stating that there is insufficient data to recommend either for or against the use of IVM in COVID-19 patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…No additional articles were retrieved from the reference lists of the included studies. Of the 21 included studies, 04 were available as preprints upon the time of submission of the present study [45][46][47][48].…”
Section: Search Resultsmentioning
confidence: 99%
“…In nine of them, the registration was done after the beginning of recruitment, in one of them the recruitment period was not mentioned, and the protocols of three studies could not be retrieved for the registration date to be checked. In eight studies, there were amends in the protocol after the registration [19,45,47,48,49,50,51,52]. * The nal sample for adverse effects is different to the nal sample for our primary outcomes ** This arm was not included in the meta-analysis 1 Lopinavir/ritonavir.…”
Section: Study and Patients' Characteristicsmentioning
confidence: 99%
“…No additional articles were retrieved from the reference lists of the included studies. Of the 21 included studies, 04 were available as preprints upon the time of submission of the present study [45][46][47][48].…”
Section: Search Resultsmentioning
confidence: 99%